-Z Acceptance of Mobile Banking for Sharia Bank: Do TAM-Model, Religiousity Intention, and Security Variables Matter? - Siti Khomsatun; Siti Salmah; Tri Nadia; Zubaidah Taslimah; Nova Dilsantuah (Tazkia Islamic Finance and Business Review, 2024)
This research aims to obtain empirical evidence regarding the acceptance and use of mobile banking at Bank Syariah Indonesia (BSI) by Generation Z, as well as proving what factors encourage Generation Z customers to adopt mobile banking in BSI. This research collected data from 100 BSI customers by Generation Z in Bogor, Indonesia. The research adopts Structural Equation Model-Partial Least Square (SEM-PLS) to link perceived usefulness, perceived ease of use, religiosity, satisfaction, security, intention to use and adoption of mobile banking. The results of this research reveal that the integration of the Technology Acceptance Model (TAM), Religious Intention Model and security variables in the Technology Based Factor (TBF) provides a more comprehensive explanation regarding the adoption of mobile banking by Generation Z customers of BSI. In addition to perceived usefulness and perceived ease of use, the results of this study emphasize the importance of security in mobile banking adoption. This research provides implications for BSI managers to improve their adoption of mobile banking services. Bank management needs to place special emphasis on security aspects in the development and promotion of Mobile Banking, as well as identify and implement effective security measures to protect customer data and transactions. This research is the first attempt to integrate the TAM model, Religious Intention Model and security variables in TBF to assess BSI mobile banking adoption.